Fast magnetically driven electrodeposition of amorphous metal oxide water oxidation catalysts from carbon-coated metallic nanoparticles1. Issue 31 (21st August 2015) - Zhu, Jing; Lambert, François; Policar, Clotilde; Mavré, François; Limoges, Benoît
<x xml:space="preserve">Abstract</x> Amorphous metal-based catalytic films for water oxidation were obtained from anodic polarization of carbon-coated metal nanoparticles.